2017
DOI: 10.1016/j.ejps.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib/gefitinib microspheres loaded polyurethane constructs as drug-eluting stent coating

Abstract: One of the complications of bronchotracheal cancer is obstruction of the upper airways. Local tumor resection in combination with an airway stent can suppress intraluminal tumor (re)growth. We have investigated a novel drug-eluting stent coating for local release of the anticancer drug gefitinib. A polyurethane (PU) sandwich construct was prepared by a spray coating method in which gefitinib was embedded between a PU support layer of 200 μm and a PU top layer of 50-200 μm. Gefitinib was either embedded in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…4 . Pure GFT showed characteristic intense peaks at 19.3°, 20.6°, 22.5°, 24°, 38.1° and 44.3° as reported in literature ( Chen et al, 2017 ). The sharp peaks of GFT disappeared completely in GFT loaded PLGA-NPs and GFT loaded CS-PLGA-NPs, indicating that GFT was dispersed molecularly with the polymer in NPs.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…4 . Pure GFT showed characteristic intense peaks at 19.3°, 20.6°, 22.5°, 24°, 38.1° and 44.3° as reported in literature ( Chen et al, 2017 ). The sharp peaks of GFT disappeared completely in GFT loaded PLGA-NPs and GFT loaded CS-PLGA-NPs, indicating that GFT was dispersed molecularly with the polymer in NPs.…”
Section: Resultssupporting
confidence: 75%
“…However, due to charge attraction between drug and chitosan in GFT loaded CS-PLGA-NPs exhibited more sustained release of drug in comparison to GFT loaded PLGA-NPs ( Fig. 5 ) ( Chen et al, 2017 ). The release data was fitted to various kinetic models in order to know release mechanism of GFT from GFT loaded PLGA-NPs and GFT loaded CS-PLGA-NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The chemotherapy drug gefitinib has been embedded between PU support and top layers using spray coating to form a drug-eluting stent for bronchotracheal cancer; 44 when the drug was embedded as crystals, release was recorded for 7-21 days, but when embedded into poly(lactic-co-glycolic acid) (PLGA) microspheres, a sustained release >6 months was noted (Fig. 4).…”
Section: Drug Delivery Vehiclesmentioning
confidence: 99%
“…(a) Release of tumour suppressing drug gefitinib from PU constructs loaded with gefitinib-PLGA microspheres; (b) schematic of bronchotracheal stent to provide long-term release of this drug 44. …”
mentioning
confidence: 99%
“…They have concluded the drug was released with a diffusion mechanism, where it was observed that the drug release rate is increased with the drug content. There are some devices to better control drug release profiles, like the use of drug delivery carriers [21], micro-sponges for hydrophobic drugs [22], or the use of barriers layers of a polymer without drug [16,23]. In the study [13], Vahedi et al have revealed that the flow conditions influence the release profile by acting on the penetration depth of the fluid.…”
Section: Introductionmentioning
confidence: 99%